2020
DOI: 10.1002/trc2.12077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lighting variability on locomotion in posterior cortical atrophy

Abstract: Introduction Clinical reports describe patients with Alzheimer's disease (AD) exhibiting atypical adaptive walking responses to the visual environment; however, there is limited empirical investigation of such behaviors or factors modulating their expression. We aim to evaluate effects of lighting‐based interventions and clinical presentation (visual‐ vs memory‐led) on walking function in participants with posterior cortical atrophy (PCA) and typical AD (tAD). Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This could be because PCA affects visual processing more than tAD, and therefore the effects of this disease are more prominent in a trial such as this. This trend has also been identified by previous research done in the same program of work at Pedestrian Accessibility Movement Environment Laboratory (PAMELA), which found that participants with early stage PCA performed worse than people with tAD (Yong et al, 2020). Therefore, because the gait of participants with is more easily distinguishable from "normal" gait than the gait of participants with tAD, the model does not confuse PCA with controls as often as it confuses tAD with controls.…”
Section: Prediction Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…This could be because PCA affects visual processing more than tAD, and therefore the effects of this disease are more prominent in a trial such as this. This trend has also been identified by previous research done in the same program of work at Pedestrian Accessibility Movement Environment Laboratory (PAMELA), which found that participants with early stage PCA performed worse than people with tAD (Yong et al, 2020). Therefore, because the gait of participants with is more easily distinguishable from "normal" gait than the gait of participants with tAD, the model does not confuse PCA with controls as often as it confuses tAD with controls.…”
Section: Prediction Resultssupporting
confidence: 69%
“…Secondly, while some previous studies have analyzed different types of dementia (Mc Ardle et al, 2020), previous studies ignore the differences between types of dementia and either focus on one type of dementia (Wittwer et al, 2013;Cedervall et al, 2014;Callisaya et al, 2017) or consider dementia without looking at its type (Marquis et al, 2002;Wang et al, 2006). Furthermore, to our knowledge, gait of people with PCA has only been analyzed by previous research in this line of investigation (Carton et al, 2016;Ocal et al, 2017;Yong et al, 2018Yong et al, , 2020McCarthy et al, 2019;McCarthy et al, Unpublished 1 ). This research has found that some patients with dementia show a consistent pattern of hesitation (which can be identified from step times) when navigating complex routes (McCarthy et al, 2019;Yong et al, 2020).…”
Section: Dementia Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…through digital presentation). Patients may exhibit difficulties with navigation, becoming lost in familiar environments and negotiating escalators, stairs and flooring with reflective surfaces, patterns and shadows [33]. The above difficulties may relate to early visuospatial and visuoperceptual abnormalities owing to parieto-occipital and occipito-temporal atrophy [23] along with more basic visual dysfunction arising from occipital damage [34,35].…”
Section: Clinical Evaluationmentioning
confidence: 99%